.NET Gadgeteer: A New Platform for K-12 Computer Science Education - Hodges, Steve; Scott, James; Sentance, Sue; Miller, Colin; Villar, Nicolas; Schwiderski-Grosche, Scarlet; Hammil, Kerry; Johnston, Steven (SIGCSE '13 Proceedings of the 44th ACM Technical Symposium on Computer Science Education, 2013)
In this paper we present the features of a new physical device prototyping platform called Microsoft .NET Gadgeteer along with our initial experiences using it to teach computer science in high schools. Gadgeteer makes it easy for newcomers to electronics and computing to plug together modules with varied functionality and to program the resulting system's behavior. We believe the platform is particularly suited to teaching modern programming concepts such as object-oriented, event-based programming and it could be a timely addition to established teaching tools given the current interest in improving high school computer science education in some regions. We have run a number of pilot studies in the US and in the UK with students of varying age and ability. Our results indicate that the tangible and expressive nature of Gadgeteer helps to engage and motivate a diverse set of students. We were also pleasantly surprised by the level of polish and sophistication of the devices which were built. We hope to further explore the potential of Gadgeteer for teaching in future work and we encourage others to build on our experiences.